DEVELOPMENT OF KEY COMPETENCIES OF PUPILS TECHNICAL VOCATIONAL EDUCATION - JUHASOVA, Jana (Journal of Technology and Information Education, 2014)
The aim of this paper is to point out the possibility of the development of key competencies in the teaching of technical vocational education. By development of key competencies we contribute to lifelong learning, the process of constant change and the amount of the further development in our society.
Keywords: key competencies; students; teaching method